Utjecaj preduzeća informaciono-komunikacionih tehnologija na privredni razvoj Bosne i Hercegovine / Impact of Information - Communication Technology Enterprises on Economics Development in Bosnia and Herzegovina - Čizmić, Elvir; Čengić, Sanjin; Šunje, Aziz (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The aim of the research is to determine how enterprises in information – communication technology (ICT) influence on development dynamic of the Fourth industrial revolution. ICT sector previously did not have significant importance as it has now. Without enterprises in ICT industry, it is impossible to carry out Fourth industrial revolution, thus it is important to give particular emphasis to this industry. ICT industry is one of the most perspective industries for development, and it is able to become significant in terms of creating new jobs, increasing export and competences, as well as generating gross domestic product with proper management. The paper provides recommendations which can be used to make better environment for ICT industry, which might lead to significant improvement of situation in the economy of Bosnia and Herzegovina.